2018
DOI: 10.1016/j.jvs.2017.05.086
|View full text |Cite
|
Sign up to set email alerts
|

On the influence of wall calcification and intraluminal thrombus on prediction of abdominal aortic aneurysm rupture

Abstract: AAA wall stiffness properties are controlled by the load-bearing capacity of the noncalcified tissue portion, and low stiffness properties represent a highly degraded vulnerable wall. The presence of calcification that is contiguous with the inner wall causes severe tissue overstretching in surrounding tissue areas. The results highlight the use of additional biomechanical measures, detailing the biomechanical-structural characteristics of AAA tissue, that may be a helpful adjunct to improve the accuracy of ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…Although some scholars believe that artery wall calcification will make aneurysm stronger, we find that calcification was usually confined to a certain part of the wall, which indicates the enhancement of the local stiffness. Some studies also have shown that calcification in some aneurysms increases its rigidity and decreases its elasticity (21). The presence of calcified plaque can decline the compliance of the entire cystic wall.…”
Section: Discussionmentioning
confidence: 99%
“…Although some scholars believe that artery wall calcification will make aneurysm stronger, we find that calcification was usually confined to a certain part of the wall, which indicates the enhancement of the local stiffness. Some studies also have shown that calcification in some aneurysms increases its rigidity and decreases its elasticity (21). The presence of calcified plaque can decline the compliance of the entire cystic wall.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests, however, that ILT plays important roles in lesion enlargement and possible rupture 13 and there is motivation to include predictions of thrombus formation within an overall clinical decision rubric. Notwithstanding many prior studies on the biosolid or biofluid mechanics of ILT in AAAs, both idealized and patient-specific 57,1114 , the pronounced patient-to-patient variability in lesion geometry has delayed general understanding.…”
Section: Discussionmentioning
confidence: 99%
“…Over 75% of these lesions harbor an intraluminal thrombus (ILT) that tends to space-fill the dilated region of the aneurysm without encroaching on the original lumen. Notwithstanding some controversy, increasing evidence suggests that an ILT can play significant roles in the natural history of these lesions 1,2 , including contributions to potentially catastrophic rupture due to the release or activation of proteases that can locally weaken the aneurysmal wall 3,4 . Formation of an ILT depends on many factors, including concentrations of coagulation-associated plasma proteins.…”
Section: Introductionmentioning
confidence: 99%
“…However, ILT exhibits significantly different material properties than the in vivo aortic wall. ILT stiffness has been found to be independent of ILT volume and AAA diameter . Although increased ILT is reported to be correlated with reduced mean and peak wall stress, it is also associated with rupture at lower AAA diameter and lower peak wall stress .…”
Section: Limitationsmentioning
confidence: 97%